Three-Dimensional Volumetric Measurement of Endolymphatic Hydrops in Meniere's Disease - Noh, Tae-Soo; Park, Moo Kyun; Lee, Jun Ho; Oh, Seung Ha; Kim, Ji-Hoon; Song, In Chan; Suh, Myung-Whan (Frontiers in Neurology, 2021)
Objective: We used volumetric three-dimensional (3D) analysis to quantitatively evaluate the extent of endolymphatic hydrops (EH) in the entire inner ear. We tested for correlations between the planimetric and volumetric measurements, to identify their advantages and disadvantages. Methods: HYDROPS2-Mi2 EH images were acquired for 32 ears (16 patients): 16 ipsilateral ears of MD patients (MD-ears) and 16 contralateral ears. Three-T MR unit with a 32-channel phased-array coil/the contrast agent to fill the perilymphatic space and the HYDROPS2-Mi2 sequence. We calculated the EH% [(endolymph)/(endolymph+perilymph)] ratio and analyzed the entire inner ear in terms of the volumetric EH% value, but only single cochlear and vestibular slices were subjected to planimetric EH% evaluation. The EH% values were compared between MD ears and non-MD ears, to evaluate the diagnostic accuracy of the two methods. Results: The volumetric EH% was significantly higher for MD vestibules (50.76 ± 13.78%) than non-MD vestibules (39.50 ± 8.99%). The planimetric EH% was also significantly higher for MD vestibules (61.98 ± 20.65%) than non-MD vestibules (37.22 ± 12.95%). The vestibular and cochlear volumetric EH% values correlated significantly with the planimetric EH% values of the MD ear. Conclusion: Volumetric and planimetric EH measurements facilitate diagnosis of MD ears compared to non-MD ears. Both methods seem to be reliable and consistent; the measurements were significantly correlated in this study. However, the planimetric EH% overestimates the extent of vestibular hydrops by 26.26%. Also, planimetric data may not correlate with volumetric data for non-MD cochleae with normal EH% values.